Template‑assisted synthesis of molecularly imprinted polymers for the removal of methyl red from aqueous media - Syed Rizwan, Shafqat; Showkat, Ahmad Bhawani; Salma, Bakhtiar; Mohamad Nasir, Mohamad Ibrahim; Syed Salman, Shafqat (BMC, 2023)
This study entails the synthesis of molecularly imprinted polymers (MIPs) with good selectivity coefcients for azo dye as a potential sorbent material to extract azo dye from polluted aqueous media. A series of MIPs for methyl red (MR) as a template, were synthesized by changing the molar ratio of functional monomers, via precipitation polymerization format of non-covalent approach. Water-soluble functional monomer; acrylic acid (AA) was used to weave the frame work of polymers while ethylene glycol dimethacrylate (EGDMA) was utilized as crosslinking monomer. The impact of different experimental parameters, such as mole ratio of monomer (functional) to crosslinking monomer on the molecular recognition was investigated. The highly effcient and selective MR-MIP was used for the removal of spiked MR dye from different water samples. The selected imprinted polymer, MR1-MIP was able to selectively remove the MR molecules from aqueous media. A significant amount of dye was removed by MR1-MIP from the river water samples with a high degree of removal efficiency i.e. 92.25%. The imprinting factor of 3.75 for MR1-MIP indicated that the high selectivity in terms of adsorption for MR. A minimum loss of only ~3.35% in the removal efficiency within ten sequential cycles of adsorption–desorption study evidenced that MR-MIPs could be used as the most cost effective and best sorbent for the removal of MR from polluted water. Furthermore, the structural properties of MR-MIPs were characterized by FTIR and EDX, whereas TGA, SEM and BET were used to describe the thermal, morphological and surface structures of the particles, respectively.